The amino acids differences in epitopes may promote the different allergenicity of ovomucoid derived from hen eggs and quail eggs - Mengzhen Hao; Shuai Yang; Shiwen Han; Huilian Che (Food Science and Human Wellness)
Quail egg ovomucoid can inhibit activation of basophils and eosinophils, while hen egg ovomucoid has been shown to be a major allergen, named Gal d 1. At present, the differences in structure and function between two ovomucoid are unclear. We found the homology of ovomucoid in quail eggs and hen eggs reached 77 %. Compared with hen egg ovomucoid, the distribution of secondary structure was different in AA52−53, AA57−58, AA66−68, AA71−72, AA131−133, AA139−140, AA157−159 and AA184−185. Among 9 epitopes of egg ovomucoid, there were different amino acids from quail egg ovomucoid in 8 epitopes. Recombination quail egg ovomucoid had trypsin inhibition activity and quail egg ovomucoid didn’t specifically bind to serum of eggs allergic patients. Quail egg ovomucoid can significantly inhibit RBL-2H3 cells degranulation and protect cells morphology to a certain extent, indicating quail egg ovomucoid can inhibit cells activation and have potential anti-allergic effects, which is related to trypsin inhibitory activity. The difference in sensitization compare to hen egg ovomucoid may be due to amino acids differences affecting protein structure by changing antigenic epitopes.